Spa - Svetoft, Erik 1988- (Fantagraphics Books, 2023)
"This nightmarish debut, a biting critique of consumer society and the 'wellness' industry, recalls the films of David Lynch and Lars Von Trier and the horror manga of Junji Ito"--
Translated from the Swedish
Keywords: Health resorts -- Comic books, strips, etc; Hotels -- Comic books, strips, etc; Health promotion -- Comic books, strips, etc; Hotel; Horror; Wellness; Albtraum; Horror comic books, strips, etc; Comics (Graphic works); Comic; Black humor; Graphic novels; Horror comics